2014
DOI: 10.1007/5584_2014_82
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of DNA Repair Genes and Lung Cancer in Chromium Exposure

Abstract: Chromium is a well known carcinogen involved in the lung cancer development. Polymorphism of some of the DNA repair genes may be associated with elevated risk of cancerous transformation. In the present study, we investigated the polymorphisms of the following selected members of the base and nucleotide excision repair genes: XPC (Lys939Gln), XPD (Lys751Gln), XRCC1(Arg399Gln), and hOGG1(Ser326Ser), and the risk they present toward the development of lung cancer, with emphasis on the effect of chromium exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…These publications concerned about five BER pathway gene, including X-Ray Repair Cross Complementing 1 (XRCC1), Apurinic/Apyrimidinic Endodeoxyribonuclease 1 (APEX1), DNA Ligase 1 (LIG1), 8-Oxoguanine DNA Glycosylase (OGG1) and MutY DNA Glycosylase (MUTYH) gene. In Table 1 , characteristics and genotype frequency distributions of all enrolled studies for BER pathway gene were showed, including XRCC1 -rs1799782/rs25487 ( 35 - 59 ), rs25489/rs3213245 ( 60 - 84 ), rs3547/rs915927 ( 85 - 90 ), PARP1 -rs1136410 ( 87 , 91 - 94 ), APEX1 -rs1130409/rs1760944/rs2307486 ( 42 , 43 , 47 , 74 , 76 , 79 , 80 , 89 , 92 , 95 - 101 ), LIG1 -rs156641/rs20579/rs20581/rs3730931/rs439132 ( 64 , 71 , 102 , 103 ), OGG1 -rs1052133 ( 43 , 47 , 49 , 70 , 72 , 74 , 84 , 85 , 89 , 92 , 104 - 126 ) and MUTYH -rs3219489 ( 104 , 115 , 118 , 127 ) polymorphisms, and the selection process of current work was described in Figure 1 . For this study, we performed each process along with PRISMA 2009 checklist ( Table 2 ), and with the aid of NOS, we also assessed each enrolled study, most of the enrolled study is higher than 7 star, which represented the good quality ( 129 ).…”
Section: Resultsmentioning
confidence: 99%
“…These publications concerned about five BER pathway gene, including X-Ray Repair Cross Complementing 1 (XRCC1), Apurinic/Apyrimidinic Endodeoxyribonuclease 1 (APEX1), DNA Ligase 1 (LIG1), 8-Oxoguanine DNA Glycosylase (OGG1) and MutY DNA Glycosylase (MUTYH) gene. In Table 1 , characteristics and genotype frequency distributions of all enrolled studies for BER pathway gene were showed, including XRCC1 -rs1799782/rs25487 ( 35 - 59 ), rs25489/rs3213245 ( 60 - 84 ), rs3547/rs915927 ( 85 - 90 ), PARP1 -rs1136410 ( 87 , 91 - 94 ), APEX1 -rs1130409/rs1760944/rs2307486 ( 42 , 43 , 47 , 74 , 76 , 79 , 80 , 89 , 92 , 95 - 101 ), LIG1 -rs156641/rs20579/rs20581/rs3730931/rs439132 ( 64 , 71 , 102 , 103 ), OGG1 -rs1052133 ( 43 , 47 , 49 , 70 , 72 , 74 , 84 , 85 , 89 , 92 , 104 - 126 ) and MUTYH -rs3219489 ( 104 , 115 , 118 , 127 ) polymorphisms, and the selection process of current work was described in Figure 1 . For this study, we performed each process along with PRISMA 2009 checklist ( Table 2 ), and with the aid of NOS, we also assessed each enrolled study, most of the enrolled study is higher than 7 star, which represented the good quality ( 129 ).…”
Section: Resultsmentioning
confidence: 99%
“…Lindsay, et al (2017) evaluated CTC prognostic value based on their number, phenotype and molecular profiling in patients with advanced NSCLC [33] and found that more than five CTCs per 10ml of blood was an independent factor associated with lower overall survival. lung cancer treatment, the analytical specificity and clinical outcome of diagnostic methods must be analyzed in prospective studies in order to obtain the data required for their introduction and use in the daily management of lung cancer patients [49,50]. Liquid biopsy could have a great potential for the treatment not only of lung cancer patients.…”
Section: Ctcs and Ctc Clusters In Lung Cancermentioning
confidence: 99%